Second trimester termination of pregnancy complicated with multiple fetal abnormalities and also placenta percreta - Babacan, Ali; Yılmaz, Ali; Akpak, Yaşam Kemal; Müngen, Ercüment; Gün, İsmet and Atay, Vedat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We read with great interest the article by Matsuzaki S and et al., in which the authors presented a case series named “Successful management of placenta percreta by cesarean hysterectomy with transverse uterine fundal incision”.